Digital Education as a Strategy for the Protection of Intellectual Property Rights - Cristina LAZARIUC (Eastern European Journal of Regional Studies, 2021)
The spiritual, scientific and cultural potential of society have always been the driving force of sustainable development, which determines the economic competitiveness of any state. Today we are witnessing a race of "digital armament", in which human rights are becoming less and less valuable, including intellectual property rights, which are systematically subjected to cyber-attacks by "data thieves". In this race, both IT giants and users with a high degree of digital literacy are driven by the maxim "purpose excuses the means", namely they admit that they may violate the limits of privacy, the limits of the principle of confidentiality, the limits of data integrity, the safety of persons, the limits of private property, including intellectual property, and all these in the name of profit. Under these conditions, the development of an efficient ecosystem for guaranteeing intellectual property rights, adapted to meet the challenges of the digital economy, requires both a strengthened regulatory environment and better competences. In this context, this article aims to address digital education, both as a mandatory requirement and objective to be achieved in the process of human adaptation to the challenges of the digital revolution, and as a strategy, whose concrete steps would ensure better protection of intellectual property rights, through the digital competences it forms.